Food - Inglis, David (Critical concepts in social sciences., 2008)
In the last five years or so, there has been a huge explosion of scholarly work on the history of food and, likewise, pressing problems such as food scares and genetic modification, as well as anorexia and obesity, have become increasingly present in the public consciousness. Drawing on a wide variety of disciplines, this fascinating four-volume collection covers anthropology, sociology, psychology, history, cultural history, land economy, and, outside of the arts and social sciences, disciplines such as health sciences and health economics. An engaging and comprehensive reference, it is undoubtedly a highly useful resource for both student and scholar alike.